Kidneys for Jesus: Religious Motivations for Organ Donation - Karim, Serena (Stimulus: A Medical Humanities Journal, 2023)
Several organ transplantation studies have stressed the healthcare team’s obligation to moral decision-making when evaluating candidates for living donation. To ensure that donors are not subject to exploitation, transplant professionals assess psychosocial influences and motivations to give. While citing religious motivations is neither uncommon nor controversial, the validity of spiritual leadership in organ donation remains vague. In this paper, I define what makes religious motivations for organ donation legitimate, and consider the degrees of involvement a spiritual leader may have through this process. I consider two Christian leaders who both mobilize their religious audiences in efforts to shorten the kidney waitlist, then I evaluate evidence of financial, familial, social, and spiritual pressures between them and potential donors. I find that religious leaders may act as spiritual and educational guides, but should not be personally involved in their followers’ donation journeys. I also find that candidates involved in faith-based group donations are particularly susceptible to coercion from peers and leaders alike. Understanding that spiritual leadership in organ donation is possible may help transplant centers better discern which motivations are legitimate, and even invite more well-intentioned candidates through ethical, faith-based dialogues.